Effects of cigarette smoking cessation on breastfeeding duration - Higgins, Tara M. (Oxford University Press, 2010)
INTRODUCTION: The purpose of this study was to use data from controlled trials to examine whether smoking cessation increases breastfeeding duration. Correlational studies have confirmed associations between smoking status and breastfeeding duration, but whether smoking cessation increases breastfeeding duration has not been established. METHODS: Participants (N = 158) were smokers at the start of prenatal care who participated in controlled trials on smoking cessation. Women were assigned to either an incentive-based intervention wherein they earned vouchers exchangeable for retail items by abstaining from smoking or a control condition where they received comparable vouchers independent of smoking status. Treatments were provided antepartum through 12-week postpartum. Maternal reports of breastfeeding collected at 2-, 4-, 8-, 12-, and 24-week postpartum were compared between treatment conditions. Whether women were exclusively breastfeeding was not investigated. RESULTS: The incentive-based treatment significantly increased breastfeeding duration compared with rates observed among women receiving the control treatment, with significant differences between treatment conditions observed at 8-week (41% vs. 26%; odds ratio [OR] = 2.7, 95% CI = 1.3–5.6, p = .01) and 12-week (35% vs. 17%; OR = 3.4, 95% CI = 1.5–7.6, p = .002) postpartum. No significant treatment effects on breastfeeding were observed at other assessments. Changes in smoking status mediated the effects of treatment condition on breastfeeding duration. CONCLUSIONS: These results provide evidence from controlled studies that smoking cessation increases breastfeeding duration, which, to our knowledge, has not been previously reported.